Increasing domestic financing for the HIV/AIDS response in Nigeria: a catalyst to self-reliance - Joy Nwizu, MSc; Ure Ihekanandu, MSc; Frances Ilika, MSc (Elsevier, 2022)
Background: Although Nigeria has the second largest HIV-positive population in the world, the country relies mostly on external donors for its HIV control. International donors account for over 81% of Nigeria's HIV spending, which is unsustainable and creates funding gaps that can be closed by identifying alternative domestic financing sources. The Health Policy Plus Project (implemented by Palladium), funded by the US Agency for International Development, supported the Nigerian government between July, 2020, and June, 2021, to assess challenges to HIV financing and to collaboratively identify feasible strategies to raise domestic resources for HIV control. Methods: A two-pronged approach that included desk reviews of relevant literature and key interviews with fourteen major stakeholders from government, donor, private, partner, and civil society organisations was adopted. Stakeholders were selected on the basis of their knowledge and involvement in the country's HIV response or their history of supporting health-system strengthening activities. The multisectoral approach helped to identify robust and feasible strategies that can easily be implemented across the 36 states and the federal capital territory in the country. Findings: Challenges to HIV financing include inadequate budgetary allocation, mostly caused by government perception of the HIV programme as the responsibility of donors; delays in fund releases; inefficient use of the HIV funds; poor tracking of funds and commodity use; inadequate country ownership; and poor accountability structures. With these findings, through a collaborative and multisectoral process, 12 strategies that can mobilise up to US$ 662 million in 5 years for HIV control were identified and included in a National Domestic Resource Mobilisation Strategy, which has been adopted for implementation across the country. The strategies included increasing government budgets and execution rates for HIV control; integration of HIV into health insurance; increasing private sector and philanthropic contributions to HIV control; raising funds from diaspora bonds, local HIV commodity production; strengthening governance, efficiency, and accountability structures, and increasing Civil Society Organisations' involvement in HIV resource mobilisation and tracking. Interpretation: Overdependence on donors for disease control programmes, especially in low-income countries, is a global health problem. A multisectoral approach can be adopted by global health stakeholders to review and select appropriate and effective domestic resource mobilisation strategies with reduced contextual barriers, such as HIV integration in key universal health coverage programmes, enhancing private sector contribution, and strengthening efficiency for implementation as a global policy to mobilise health resources. Implementation of the strategies will reduce dependence on donor funds, reduce out-of-pocket payments for HIV, improve access to HIV services, and subsequently lead to improved HIV outcomes. Funding: US Agency for International Development.